2014
DOI: 10.1016/j.agee.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Biochar application rate affects biological nitrogen fixation in red clover conditional on potassium availability

Abstract: Increased biological nitrogen fixation (BNF) by legumes has been reported following biochar application to soils, but the mechanisms behind this phenomenon remain poorly elucidated.We investigated the effects of different biochar application rates on BNF in red clover (Trifolium pratense L.) Red clover was grown in mono or mixed cultures with red fescue grass (Festuca rubra L.) and plantain (Plantago lanceolata L.) at a range of different biochar application rates (0, 10, 50 and 120 t ha -1 ). In a separate ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(76 citation statements)
references
References 50 publications
2
67
2
5
Order By: Relevance
“…Recent studies suggest that K fertilization effect of biochar is critical for promoting growth, biological N fixation and competitive ability of legume species (Mia et al 2014;Oram et al 2014). In our study, the high K concentration in the peanut shell biochar may also contribute to the production response of peanuts, especially on redoxi-hydrosol which displays a very strong K deficiency.…”
Section: Fertilization Effect Of Biocharmentioning
confidence: 82%
“…Recent studies suggest that K fertilization effect of biochar is critical for promoting growth, biological N fixation and competitive ability of legume species (Mia et al 2014;Oram et al 2014). In our study, the high K concentration in the peanut shell biochar may also contribute to the production response of peanuts, especially on redoxi-hydrosol which displays a very strong K deficiency.…”
Section: Fertilization Effect Of Biocharmentioning
confidence: 82%
“…Because biochar contains ash and so adds nutrients such as K, Ca and Mg to the soil solution, increasing the pH of the soil and providing readily available nutrients for plant growth (Glaser et al, 2002). Recent studies suggest that a K fertilization effect associated with biochar is critical for promoting growth, biological N fixation and the competitive ability of legume species (Mia et al, 2014;Oram et al, 2014;Xu et al, 2015). In this study, high K concentrations in the Com and COMBI treatments may also have contributed to the peanut yield response associated with the organic amendments, where a significant increase in soil available K was observed.…”
Section: Soil Amendment Effects On Soil Nutrient Dynamics and Ghg Emimentioning
confidence: 99%
“…A more recent glasshouse study by Guerna et al (2015) demonstrated that biological N 2 fixation increases following biochar amendment, resulting from increased plant P uptake which was associated with a 360 % increase in mycorrhizal colonisation. In contrast, Mia et al (2014) suggested that improved biological N 2 fixation in red clover (Trifolium pratense L.) following biochar amendment resulted from improved K nutrition in a moderately acid soil. The authors suggest this benefit could be short term only due to the relatively high availability of K from the biochars used.…”
Section: Introductionmentioning
confidence: 97%